Wide field electromagnetic method calculation in arbitrary orientation and its effectiveness analysis - Tian, Hongjun; Qiang, Jianke; Li, Kun; Tan, Zhangkun; Zhang, Ying; Zhu, Dexiang (Frontiers in Earth Science, 2023)
The wide field electromagnetic methodE_Exobservation method requires the current source AB to be parallel to the receiver MN, but the complex terrain conditions make it difficult to meet the AB parallel MN in field construction, and there is always an azimuthal difference α between them, which will bring a large calculation error and cause distortion of the interpretation parameters if the calculation method E_Excontinues to be used. In order to tackle this problem, this paper analyzes and studies the EExobservation method and derives the calculation method of E_EMN for the wide field electromagnetic method with arbitrary observation orientation. The method is based on the intrinsic relationship between the electric field components Ex、Ey and the azimuthal difference α and derives the expression for the electric field E_MN along the MN direction, and then uses the EMN method to calculate the wide field apparent resistivity. In this paper, we design a three-layer geoelectric model algorithm and calculate the azimuthal angle difference α=0°and α=0 wide field apparent resistivity parameters, respectively. The calculation example shows that the relative error between the calculated apparent resistivity and the theoretical value is less than 1%, which verifies the correctness and validity of the method. To further verify the accuracy of the method, experimental work on azimuthal difference α was carried out next to a known well in Sichuan. The results show that: firstly, when α is 1°、3°、5°、10°and 15°, respectively, the relative error of each frequency point increases with increasing α. Secondly, when α is 1°、3°、5°、10°and 15°, respectively, the relative error of each frequency point is less than 10% when the E_MN method is used to calculate the wide field apparent resistivity value; thirdly, taking α =15°as an example, single-point inversions are performed with E_x and E_MN apparent resistivity parameters, in which the Ex inversion results are more different from the trend of the logging curve, while the EMN inversion results are relatively more consistent with the trend of the logging curve.